Kompleks Inklusi Amlodipin Besilat – β-siklodekstrin Dengan Metode Kneading - Indra Makmur; Auzal Halim; Maria Dona Oktavia; Helvia Angraeni (STIFARM Padang, 2018)
Preparation and characterization of inclusion complex of amlodipine besylat with β - cyclodextrin has been done. Preparation of the inclusion complex was carried kneading method. Formed inclusion complex was characterized by X-ray diffraction, FT - IR spectrophotometer, Scanning Electron Microscopy (SEM), and the dissolution test. Data from X-ray diffraction, FT - IR, SEM can be concluded that inclusion complexes with kneading method give the best results. The dissolution efficient results showed that the inclusion complex of amlodipine besylat - β - cyclodextrin with a kneading method increased significantly when compared with the active ingredient and the mixture of physics.